Penentuan Strategi Digital Marketing pada UMKM Mengunakan Metode SAW - Vera Angelita Vebriyanii; Rini Indriati; Rina Firliana (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2026)
The growth of digital marketing has become an important gateway for MSMEs to broaden their market visibility and strengthen product promotion. Even so, the wide range of digital marketing alternatives frequently creates uncertainty for MSME actors when determining which strategy is most relevant to their business context. This study focuses on developing a Decision Support System (DSS) that can recommend the most effective digital marketing strategy for Galih Gallery MSME through the implementation of the Simple Additive Weighting (SAW) technique. The system development follows the Waterfall approach, beginning with needs identification, followed by system design, coding, testing, and final evaluation. Research data were obtained from interviews, field observations, and questionnaire responses. Several decision indicators were used, namely implementation expenditure, market attractiveness, ease of operation, and the level of sales conversion. The application was designed as a web-based system using PHP and MySQL. The research results reveal that the system is able to process normalization, calculate criterion weights, generate preference values, and arrange strategic alternatives in ranking order automatically based on the SAW method. The Black Box testing outcome confirms that every feature operates in accordance with the expected user requirements. As a result, the system is intended to support Galih Gallery MSME in selecting digital marketing strategies through a decision-making mechanism that is more measurable, practical, and well-organized.